The ArsH Protein Product of the Paracoccus denitrificans ars Operon Has an Activity of Organoarsenic Reductase and Is Regulated by a Redox-Responsive Repressor - Sedláček, Vojtěch; Kryl, Martin; Kučera, Igor (Antioxidants (Basel, Switzerland), 2022)
Paracoccus denitrificans ArsH is encoded by two identical genes located in two distinct putative arsenic resistance (ars) operons. Escherichia coli-produced recombinant N-His6-ArsH was characterized both structurally and kinetically. The X-ray structure of ArsH revealed a flavodoxin-like domain and motifs for the binding of flavin mononucleotide (FMN) and reduced nicotinamide adenine dinucleotide phosphate (NADPH). The protein catalyzed FMN reduction by NADPH via ternary complex mechanism. At a fixed saturating FMN concentration, it acted as an NADPH-dependent organoarsenic reductase displaying ping-pong kinetics. A 1:1 enzymatic reaction of phenylarsonic acid with the reduced form of FMN (FMNH2) and formation of phenylarsonous acid were observed. Growth experiments with P. denitrificans and E. coli revealed increased toxicity of phenylarsonic acid to cells expressing arsH, which may be related to in vivo conversion of pentavalent As to more toxic trivalent form. ArsH expression was upregulated not only by arsenite, but also by redox-active agents paraquat, tert-butyl hydroperoxide and diamide. A crucial role is played by the homodimeric transcriptional repressor ArsR, which was shown in in vitro experiments to monomerize and release from the DNA-target site. Collectively, our results establish ArsH as responsible for enhancement of organo-As(V) toxicity and demonstrate redox control of ars operon.
Keywords: redox-responsive repressor; organoarsenicals; Paracoccus denitrificans; FMN; NADPH